THE RELATIONSHIP BETWEEN FAMILY SUPPORT AND SOCIAL SUPPORT WITH DIET ADHERENCE OF HYPERTENSIVE PATIENTS - Norma Sari, Hesti; Pranata, Satriya; Khoiriyah, Khoiriyah; Warsono , Warsono (Journal of Vocational Nursing, 2025)
Introduction: Hypertension is an escalating global health issue, with diet playing a critical role in its management by limiting salt and saturated fat intake while increasing the consumption of fruits, vegetables, and fiber. However, low patient compliance often leads to unstable blood pressure and increases the risk of complications such as stroke, heart disease, and kidney failure. This study aims to analyze the relationship between family support, social support, and diet adherence among hypertensive patients. Methods: This study employed a descriptive survey approach with a cross-sectional research design, conducted among hypertensive patients at the Margorejo Pati Health Center. A total of 40 participants were selected using purposive sampling techniques. Data were collected using a Family Support Questionnaire, a Social Support Questionnaire, and a Hypertension Diet Adherence Questionnaire. The Spearman Rank Correlation test was used to determine the relationship between the variables. Results: The bivariate analysis revealed a strong correlation between family support and diet adherence among hypertensive patients, with a p-value of 0.000 (p ≤ 0.05) and a correlation strength of r = 0.979, indicating a very strong and positive relationship. Additionally, social support was significantly associated with diet adherence, with a p-value of 0.000 (p ≤ 0.05) and a correlation strength of r = 0.912, demonstrating a very strong positive correlation. Conclusions: The findings indicate that both family and social support are strongly and positively correlated with the dietary adherence of hypertensive patients. Based on these findings, it is recommended to enhance family involvement in patient dietary management.